Thyroid Function In Vitiligo - Chanda M; Dey S K; Gangopadhyay D N; Choudhuri S C; Roy A (Wolters Kluwer Medknow Publications, 1996)
Fifty vitilgo patients were studied clinically and subjected to thyroid function tests and estimation of glucose and choteserol. Clinical analysis revealed the incidence among new patients to be1.1%. The male/female ratio was 1:1.28. Patient up to 30 years contributed 76%. Vitilgo was obtained in12% and family history of atopy was found in 24% of patients: History of atopy was present in 16% cases. Halo nevus (1 Case), alopecia areata (2 cases) were associated with vitiligo in the study. Abnormality of thyroid function test was detected in 4 cases: it denoted hyperthyroidism in 3 cases and hypothyroidism in1 case. High level of glucose was seen in 3 cases. Cholesterol estimation showed high level in 2 cases.